Escin's Action on Bradykinin Pathway: Advantageous Clinical Properties for an Unknown Mechanism? - Gianmarco Marcianò; Cristina Vocca; Demirhan Dıraçoğlu; Rotinda Özdaş Sevgin; Luca Gallelli (MDPI AG, 2024)
Escin, extracted from horse chestnut (Aesculus hippocastanum) has anti-edema and anti-inflammatory effects. It is used to treat several clinical conditions, including venous insufficiency, pain, inflammation, and edema. Considering escin's pharmacodynamic, the inhibition of the bradykinin pathway represents a particular effect, decreasing the local edema and conferring an advantage in comparison to other compounds. In this narrative review, we described the effects of escin considering its effects on bradykinin pathway.